International Citizen Service Entrepreneur (ICSE) project of voluntary service overseas - Shuvro, Asif Iqbal (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.